Forces during cellular uptake of viruses and nanoparticles at the ventral side - Wiegand, Tina; Fratini, Marta; Frey, Felix; Yserentant, Klaus; Liu, Yang; Weber, Eva; Galior, Kornelia; Ohmes, Julia; Braun, Felix; Herten, Dirk-Peter; Boulant, Steeve; Schwarz, Ulrich S.; et al. (Nature Communications, 2020)
Many intracellular pathogens, such as mammalian reovirus, mimic extracellular matrix motifs to specifically interact with the host membrane. Whether and how cell-matrix interactions influence virus particle uptake is unknown, as it is usually studied from the dorsal side. Here we show that the forces exerted at the ventral side of adherent cells during reovirus uptake exceed the binding strength of biotin-neutravidin anchoring viruses to a biofunctionalized substrate. Analysis of virus dissociation kinetics using the Bell model revealed mean forces higher than 30 pN per virus, preferentially applied in the cell periphery where close matrix contacts form. Utilizing 100 nm-sized nanoparticles decorated with integrin adhesion motifs, we demonstrate that the uptake forces scale with the adhesion energy, while actin/myosin inhibitions strongly reduce the uptake frequency, but not uptake kinetics. We hypothesize that particle adhesion and the push by the substrate provide the main driving forces for uptake.